2017
DOI: 10.21276/aimdr.2017.3.2.sg14
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Perforation Peritonitis in a Tertiary Health Care Centre of Central India

Abstract: Background: Perforation peritonitis is one of the commonest emergencies encountered in surgical patients in India. The etiology of this condition in tropical countries is different than those from the western countries. Presents study highlights the spectrum of perforation peritonitis seen in the department of general surgery in Index medical college, Indore (M.P.). Methods: A prospective cum retrospective study was performed on 227 patients of perforation peritonitis over a period of 3 years in the department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
3
6
0
Order By: Relevance
“…12 There is some variations observed in previous studies where duodenal perforation found to be the commonest cause of perforation. 8,11,13 Gastro-duodenal perforation was commonest site of perforation followed by appendicular and ileal perforation in our study which is constant with previous studies. 7,12 In contrast some studies also show small bowel perforation as the commonest site.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…12 There is some variations observed in previous studies where duodenal perforation found to be the commonest cause of perforation. 8,11,13 Gastro-duodenal perforation was commonest site of perforation followed by appendicular and ileal perforation in our study which is constant with previous studies. 7,12 In contrast some studies also show small bowel perforation as the commonest site.…”
Section: Discussionsupporting
confidence: 90%
“…17,18 Overall mortality rate was low 7.4% in present series of study of 108 cases, which was also noticed in previous studies. 7,9,11,13 In contrast mortality rate is 15-30% is observed various other studies. 12,18…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…64% of the study population presented after 24 hours of symptom onset. 12 A largest single centre study on perforation peritonitis was carried out by Malik P over 1400 cases between January 2011 and December 2013. 62% of study population presented after 24 hours of symptom onset.…”
Section: Discussionmentioning
confidence: 99%